An Alternative Method for Long-Term Monitoring of Thai Historic Pagodas Based on Terrestrial Laser Scanning Data: A Case Study of Wat Krachee in Ayutthaya - Peerasit Mahasuwanchai; Chainarong Athisakul; Phasu Sairuamyat; Weerachart Tangchirapat; Sutat Leelataviwat; Somchai Chucheepsakul (Advances in Civil Engineering)
This article presents an alternative method for the long-term monitoring of heritage pagodas in Thailand. In this method, terrestrial laser scanning (TLS) is used in combination with permanent survey markers. The Wat (temple) Krachee in the Ayutthaya Province of Thailand was chosen as a case study. This temple has several fantastic elements, including an inverted bell-shaped pagoda, two intertwined trees growing within it, and a chamber inside the pagoda. The preservation team working on the pagoda encountered a challenging problem and faced a decision to trim or not to trim the tree since it has a long-term effect on the pagoda’s structural stability. A high-accuracy terrestrial laser scanner was used to collect three-dimensional point cloud data. Permanent survey markers were constructed in 2018 to be used in long-term monitoring. The 3D surveying of the temple and the monitoring of the pagoda were carried out in five sessions during a period ending in 2020. A point cloud data analysis was performed to obtain the current dimensions, a displacement analysis, and the pagoda leaning angle. The results revealed that the terrestrial laser scanner is a high-performance piece of equipment offering efficient evaluation and long-term monitoring. However, in this study, permanent survey markers were also required as a benchmark for constraining each monitoring session. The 3D point cloud models could be matched with the assumption model elements to evaluate the damaged shape and to determine the original form. The significant elements of an inverted bell-shaped pagoda were investigated. Trimming the tree was found to cause the leaning angle of the pagoda to decrease. An equation was developed for predicting the leaning angle of the Wat Krachee pagoda for preservation and restoration planning in the future. From the results of this study, it is recommended that periodic monitoring should continue in order to preserve Thai pagodas in their original forms.